Implementation of the new EU IVD regulation: urgent initiatives are needed to avert impending crisis - Cobbaert, Christa; Capoluongo, Ettore D.; Vanstapel, Florent; Bossuyt, Patrick M. M.; Bhattoa, Harjit Pal; Nissen, Peter Henrik; Orth, Matthias; Streichert, Thomas; Young, Ian S.; Macintyre, Elizabeth; Fraser, Alan G.; Neumaier, Michael (Clinical chemistry and laboratory medicine, 2022)
Laboratory medicine in the European Union is at the dawn of a regulatory revolution as it reaches the end of the transition from IVDD 98/79/EC (https://eur-lex.eur-opa.eu/legal-content/EN/TXT/?uri=CELEX%3A31998L0079&qid=1628781352814) to IVDR 2017/746 https://eur-lex.europa.eu/eli/reg/2017/746. Without amendments and contingency plans, implementation of the IVDR in May 2022 will lead the healthcare sector into uncharted waters due to unpreparedness of the EU regulatory infrastructure. Prospective risk analyses were not made by the European Commission, and if nothing happens it can be anticipated that the consequences will impact all stakeholders of the medical test pipeline, may seriously harm patients and may prevent caregivers from making appropriate clinical decisions due to non-availability of medical tests. Finally, it also may discourage manufacturers and academia from developing specialty tests, thereby hampering innovation in medical diagnostic care. We hereby inform laboratory professionals about the imminent diagnostic collapse using testimonies from representative stakeholders of the diagnostic supply chain and from academia developing innovative in-house tests in domains of unmet clinical needs. Steps taken by the EFLM Task Force on European Regulatory Affairs, under the umbrella of the Biomedical Alliance in Europe, will be highlighted, as well as the search for solutions through dialogue with the European Commission. Although we recognize that the IVDR promotes positive goals such as increased clinical evidence, surveillance, and transparency, we need to ensure that the capabilities of the diagnostic sector are not damaged by infrastructural unpreparedness, while at the same time being forced to submit to a growing bureaucratic and unsupportive structure that will not support its “ droit d’exister ”.